Favorable Cardiovascular Risk Profile Is Associated With Lower Healthcare Costs and Resource Utilization: The 2012 Medical Expenditure Panel Survey. (March 2016) - Valero-Elizondo, Javier; Salami, Joseph A.; Ogunmoroti, Oluseye; Osondu, Chukwuemeka U.; Aneni, Ehimen C.; Malik, Rehan; Spatz, Erica S.; Rana, Jamal S.; Virani, Salim S.; Blankstein, Ron; Blaha, Michael J.; Veledar, Emir; et al.
Abstract : Background—: The American Heart Association's 2020 Strategic Goals emphasize the value of optimizing risk factor status to reduce the burden of morbidity and mortality. In this study, we aimed to quantify the overall and marginal impact of favorable cardiovascular risk factor (CRF) profile on healthcare expenditure and resource utilization in the United States among those with and without cardiovascular disease (CVD). Methods and Results—: The study population was derived from the 2012 Medical Expenditure Panel Survey (MEPS). Direct and indirect costs were calculated for all-cause healthcare resource utilization. Variables of interest included CVD diagnoses (coronary artery disease, stroke, peripheral artery disease, dysrhythmias, or heart failure), ascertained by International Classification of Diseases, Ninth Edition, Clinical Modification codes, and CRF profile (hypertension, diabetes mellitus, hypercholesterolemia, smoking, physical activity, and obesity). Two-part econometric models were used to study expenditure data. The final study sample consisted of 15 651 MEPS participants (58.5±12 years, 54% female). Overall, 5921 (37.8%) had optimal, 7002 (44.7%) had average, and 2728 (17.4%) had poor CRF profile, translating to 54.2, 64.1, and 24.9 million adults in United States, respectively. Significantly lower health expenditures were noted with favorable CRF profile across CVD status. Among study participants with established CVD, overall healthcare expenditures with optimal and average CRF profile were 5946 and 3731 less compared with those with poor CRF profile. The respective differences were 4031 and 2560 in those without CVD. Conclusions—: Favorable CRF profile is associated with significantly lower medical expenditure and healthcare utilization among individuals with and without established CVD. Abstract : Supplemental Digital Content is available in the text.